2015
DOI: 10.1073/pnas.1417605112
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and determination of absolute configurations of insect-produced methyl-branched hydrocarbons

Abstract: Although the effects of stereochemistry have been studied extensively for volatile insect pheromones, little is known about the effects of chirality in the nonvolatile methyl-branched hydrocarbons (MBCHs) used by many insects as contact pheromones. MBCHs generally contain one or more chiral centers and so two or more stereoisomeric forms are possible for each structure. However, it is not known whether insects biosynthesize these molecules in high stereoisomeric purity, nor is it known whether insects can dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 66 publications
0
35
0
3
Order By: Relevance
“…In S. geminata workers, there were 16 alkanes and 12 alkenes with 17 – 35 carbon chain lengths as shown in Table . Methyl‐alkanes in S. geminata workers should be all the ( R )‐enantiomer . In the dark form, major peaks 2 , 7 , 8 , 12 , 13 , 25 were heneicosane, ( Z )‐9‐tricosene, tricosane, ( Z )‐9‐pentacosene, pentacosane, hentriacontene, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…In S. geminata workers, there were 16 alkanes and 12 alkenes with 17 – 35 carbon chain lengths as shown in Table . Methyl‐alkanes in S. geminata workers should be all the ( R )‐enantiomer . In the dark form, major peaks 2 , 7 , 8 , 12 , 13 , 25 were heneicosane, ( Z )‐9‐tricosene, tricosane, ( Z )‐9‐pentacosene, pentacosane, hentriacontene, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…It was unexpected that the primer and releaser effects would appear to be mediated by different enantiomers, or that the (S)-enantiomer would be active at all, because, as noted in the Introduction, a recent study has suggested that the large majority of methyl-branched hydrocarbons in insect cuticular lipids are likely to have the (R)-configuration (Bello et al, 2015). However, our results are consistent with the study by Sharma et al (2015), who showed that the sensilla present on the antennae of Camponotus ants respond to both (R)-and (S)-enantiomers and that ants are able to discriminate between these enantiomers in behavioral tests.…”
Section: Discussionmentioning
confidence: 99%
“…For the olive fly, Dacus oleae, males and females produce a racemic mixture of their spiroacetal pheromone olean, but the sexes respond differently to the two enantiomers (Haniotakis et al, 1986). Unfortunately, the technology does not yet exist to determine the enantiomeric ratio of the ∼100 ng quantities of 3-MeC 31 that are present on the cuticle of a L. niger queen by analytical chemistry methods (Bello et al, 2015). Thus, our interpretation of the results described above remains somewhat speculative, until the enantiomer or blend of enantiomers produced by L. niger queens can be conclusively determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general though methyl branched fatty acids display small specific rotations, which decrease as the branch point is moved to the middle of the chain. 30 Therefore, based on Van't Hoff's rule of optical superposition, the contribution of the sidechain to the overal specific rotation will be mininal for 6 and 7 . Thus, while the configuration of the sidechain remains unassigned, the configuration of spirocycohexadienylisoxazoline cores in 6 and 7 is proposed as 1 S ,6 R as well.…”
mentioning
confidence: 99%